Development of Digital Flipbook Media for Smart Fathers, Parenting - Nur Riska; Irma Yuliantina; Karima Salihanisa; Dhea Yuwono Putri; Syifa Andina; Dwi Purwestri Sri Suwarningsih; Yuli Yana; Lucy Herny (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research aims to develop and test the feasibility of learning media based on flipbook digital with the theme